Differentially expressed genes in mycorrhized and nodulated roots of common bean are associated with defense, cell wall architecture, N metabolism, and P metabolism. - Kalpana Nanjareddy; Manoj-Kumar Arthikala; Brenda-Mariana Gómez; Lourdes Blanco; Miguel Lara (PLoS ONE)
Legumes participate in two important endosymbiotic associations, with phosphorus-acquiring arbuscular mycorrhiza (AM, soil fungi) and with nitrogen-fixing bacterial rhizobia. These divergent symbionts share a common symbiotic signal transduction pathway that facilitates the establishment of mycorrhization and nodulation in legumes. However, the unique and shared downstream genes essential for AM and nodule development have not been identified in crop legumes. Here, we used ion torrent next-generation sequencing to perform comparative transcriptomics of common bean (Phaseolus vulgaris) roots colonized by AM or rhizobia. We analyzed global gene expression profiles to identify unique and shared differentially expressed genes (DEGs) that regulate these two symbiotic interactions, and quantitatively compared DEG profiles. We identified 3,219 (1,959 upregulated and 1,260 downregulated) and 2,645 (1,247 upregulated and 1,398 downregulated) unigenes that were differentially expressed in response to mycorrhizal or rhizobial colonization, respectively, compared with uninoculated roots. We obtained quantitative expression profiles of unique and shared genes involved in processes related to defense, cell wall structure, N metabolism, and P metabolism in mycorrhized and nodulated roots. KEGG pathway analysis indicated that most genes involved in jasmonic acid and salicylic acid signaling, N metabolism, and inositol phosphate metabolism are variably expressed during symbiotic interactions. These combined data provide valuable information on symbiotic gene signaling networks that respond to mycorrhizal and rhizobial colonization, and serve as a guide for future genetic strategies to enhance P uptake and N-fixing capacity to increase the net yield of this valuable grain legume.